2021
DOI: 10.21203/rs.3.rs-472215/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy of Bedaquiline in the Treatment of Drug-resistant Tuberculosis: A Systematic Review and Meta-analysis

Abstract: Background: Drug-resistant TB (DR-TB) remains a major public health concern around the world. Bedaquiline, a novel diarylquinoline, was added into WHO recommended all-oral regimen for patients with multidrug-resistant tuberculosis. We undertook a systematic review and meta-analysis to determine the effect of bedaquiline on tuberculosis treatment outcomes.Methods: We searched for relevant studies in the PubMed, Web of Science and EMBASE database for relevant studies published up to 12 Mar 2021. Stata version 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This study also found that XDR-TB patients prescribed with bedaquiline had 4.7 times higher chances of unfavourable treatment outcomes as compared to those who were on conventional therapy without bedaquiline. Contrary to this, the use of bedaquiline has been associated with favourable treatment outcomes in many randomized controlled trials ( Ahmad et al, 2018 , Wang et al, 2021 ). Similarly, BPal regimen, - in which bedaquiline is used in combination with other highly effective drugs, including novel pretomanid, - has been approved recently in view of its promising treatment success rates ( Conradie et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study also found that XDR-TB patients prescribed with bedaquiline had 4.7 times higher chances of unfavourable treatment outcomes as compared to those who were on conventional therapy without bedaquiline. Contrary to this, the use of bedaquiline has been associated with favourable treatment outcomes in many randomized controlled trials ( Ahmad et al, 2018 , Wang et al, 2021 ). Similarly, BPal regimen, - in which bedaquiline is used in combination with other highly effective drugs, including novel pretomanid, - has been approved recently in view of its promising treatment success rates ( Conradie et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Bedaquiline is the main drug in the DR-TB regimen, with the addition of four other drugs based on the patient's sensitivity. 7,8 One of the side effects of Bedaquiline on the heart is the increasing QT interval prolongation incidence that can be seen on an electrocardiogram (ECG). QT intervals refer to ventricular systole cardiac electricity and combine measurement of heart depolarization and repolarization.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, Bedaquiline (BDQ) was the first new tuberculosis drug approved by the United States Food and Drug Administration in nearly 50 years. BDQ is a gamechanger for the treatment of rifampicin-resistant tuberculosis (RR-TB) as it enabled the replacement of a long, toxic regimen with a short, all-oral regimen [1][2][3][4]. In the context of the COVID-19 pandemic, the importance of the all-oral regimen has been highlighted since it facilitates home-based care for vulnerable TB patients [5].…”
Section: Introductionmentioning
confidence: 99%